The impact of audit market concentration and market power on audit fees: a comparison of Indonesia and Singapore - Situmorang, Frans Pangeran Adri Mangaraja; Fitriany, Fitriany; Indriani, Vitria (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to investigate the effect of audit market concentration and market power on audit fees in Indonesia (high audit market concentration) and Singapore (low audit market concentration). The sample is listed companies from 2012-2015. Market concentration was calculated by the Herfindahl–Hirschman Index, while market power is the difference in market share between one audit firm and another audit firm that has the closest market share. Regression result found that the effect of market concentration on audit fees depends on the level of market competition in the country. In countries where the level of competition is low (such us Singapore), if market concentration increases, the rivalry will decrease. The remaining audit firm is not worried about losing clients because the number of players in the market has decreased and eventually dare to increase audit fees. In contrast, countries that have a high rivalry (such us Indonesia), when the market concentration increases, the competition among the remaining audit firms is still high (because there are many audit firms). As a result, the remaining audit firm gives a discounted price to win the competition and thus audit fee will decrease. However, if there are stringent regulations and strong law enforcement (like Singapore), audit fees could not be altered by market concentration, especially by market power in a form of monopoly. Audit market rivalry in Indonesia is relatively high. Hence, robust supervision and monitoring are required from authority to ensure that unfair audit fees will not emanated from the competitive audit market. Additionally, regulators need to pay attention on this topic due to the fact that unhealthy competition may create biased audit pricing that affect audit quality.